(untitled) (International Seven Journal of Health Research, 2024)
Acute aortic dissection is a potentially serious clinical condition and diagnosis is often delayed due to errors made in the patient’s first treatment. In the case reported below, one patient was hospitalized with classic symptoms of substernal pain radiating to the back, a condition that had started more than five days earlier. In the emergency room, correct care and diagnoses were carried out and the patient was referred to the surgical center. A few days after the operation, the patient returned with a new dissection, this time in the most distal part of the aorta, which was treated clinically, without surgical intervention. Care information and surgical reports were collected, and a brief review of the literature was performed to address the clinical case. The patient, after two complications, evolved well and fully recovered.